Konstruksi Makna Cantik Bagi Mahasiswi yang Memiliki Tubuh Plus-Size di Universitas Singaperbangsa Karawang - Citra, Melia; Utamidewi, Wahyu; Nayiroh, Luluatu (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by understanding how plus-size female students interpret the word beautiful amidst the dynamics of beauty standards that are constantly changing and constructed by the surrounding community, so that they often lose power over the definition of beauty itself. This study aims to (1) reveal the meaning of beauty that they adhere to, (2) map how they interpret themselves, and (3) their communication experiences amidst the stigma and stereotypes of plus-size bodies. Using a qualitative approach with a phenomenological method, the researcher conducted in-depth interview, participant observation, and documentation to comprehensively explore the informants' narratives and life experiences. The results of the study show that plus-size female students interpret beauty not only from a physical aspect, but also through self-confidence, health, uniqueness, and inner beauty. Some informants admitted to lacking self-confidence and feeling unhealthy, while others emphasized that beauty lies in self-comfort and appreciation for the body as it is. Objectification of people closest to them and media representation are dominant factors, while the views of the wider community have a more minor influence. In addition, the communication experiences of the informants are formed through the dynamics of intrapersonal communication, interpersonal communication, communication in small groups, and communication in public spaces that also influence the construction of the meaning of the body and beauty. This finding confirms that the meaning of beauty for plus-size female students is multidimensional, a complex process of externalization, objectivation, and internalization.